Evaluation of Chemical, Biological, Radiological, Nuclear, Explosives (CBRNE) Knowledge Change and Skills Confidence Among Frontline-Line Providers During the Russia-Ukraine War. (9th May 2023) - Erickson, Timothy B.; Harvin, Donell; Schmid, Alexis; Loevinsohn, Gideon; Poriechna, Anna; Martyshyn, Oleg; Kliukach, Kryrylo; Sydlowski, Meaghan; Strong, Jonathan; Kivlehan, Sean M.
Abstract: Objective: The aim of this study was to evaluate the change in knowledge and skill confidence after implementation of a chemical, biological, radiological, nuclear, and explosive (CBRNE) training course during the Russia-Ukraine War. Methods: Pre/post-test study in the Ukrainian cities of Kyiv, Dnipro, Zaporizhzhia, and Odesa. Fifteen CBRNE courses were conducted over a 3-mo period, August to October 2022. Change in knowledge and skills confidence were evaluated with pre/post-course written exams and practical skill assessments that were observed during the training exercises. Changes were analyzed based on nonparametric Wilcoxon matched-pairs signed-rank testing. Pre/post self-efficacy surveys were analyzed with McNemar's test for paired data. Course evaluations were conducted with standardized questions which assessed instruction quality, teaching relevance, knowledge gained, and post-course skills confidence. Results: A total of 523 participants registered and completed 1 of the 15 courses. Overall mean pre-course test score: 57.8% (SD 20.7%); mean post-course test score: 81.4% (SD 11.3%); participants with increasing test scores: 90.7%; mean difference in score (95% confidence interval) 23.6% (21.2%-25.9%), P < 0.0001. Pre/post self-efficacy surveys (4-point Likert scale) noted participants recognized signs and symptoms of a CBRNE incident, and necessary skills to manage CBRNE exposures, P < 0.0001. Conclusions: The implementation of this CBRNE course for front-line providers in Ukraine was successful. To our knowledge, it was the first implementation of a field course during the current Russian-Ukraine war. Future research should evaluate knowledge retention and impact of our innovative Train-the-Trainer model. Further iterations should emphasize expanding the quantity of training equipment and practical skill sessions.